2021
DOI: 10.1158/1538-7445.am2021-1374
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1374: The novel PARP1-selective inhibitor AZD5305 has reduced hematological toxicity when compared to PARP1/2 inhibitors in pre-clinical models

Abstract: Current clinical poly (ADP-ribose) polymerase (PARP) inhibitors target both PARP1 and PARP2 and they all cause clinical cytopenias with varying severity. Understanding the mechanism underlying the hematological toxicity of these agents is key for the rational design of a best-in-class molecule with greater therapeutic potential, both as monotherapy and in combination with chemotherapy. We validated the rat as a physiologically competent translational model to investigate PARP inhibitor-driven he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Notably, this differentiation was maintained and confirmed again in a more closely mimic clinical protocol with two-weekly cycles and higher dose of carboplatin ( Gill et al, 2021 ). Thus, regardless of monotherapy or in carboplatin combinations, AZD5305 has improved hematological tolerability over dual PARP1/2 inhibitors in rodents ( Gill et al, 2021 ). Findings above has confirmed the pathogenic role of PARP2-associated hematologic toxicity, thus targeting only PARP1 can retain the therapeutic benefit of non-selective PARPi, while reducing potential for hematotoxicity ( Illuzzi et al, 2022 ).…”
Section: Parp1-selective Inhibitor Azd5305mentioning
confidence: 71%
See 2 more Smart Citations
“…Notably, this differentiation was maintained and confirmed again in a more closely mimic clinical protocol with two-weekly cycles and higher dose of carboplatin ( Gill et al, 2021 ). Thus, regardless of monotherapy or in carboplatin combinations, AZD5305 has improved hematological tolerability over dual PARP1/2 inhibitors in rodents ( Gill et al, 2021 ). Findings above has confirmed the pathogenic role of PARP2-associated hematologic toxicity, thus targeting only PARP1 can retain the therapeutic benefit of non-selective PARPi, while reducing potential for hematotoxicity ( Illuzzi et al, 2022 ).…”
Section: Parp1-selective Inhibitor Azd5305mentioning
confidence: 71%
“…In rat models as a monotherapy, in comparison with olaparib, AZD5305 does not cause hematological toxicity at predicted clinically efficacious exposures, however, olaparib causes up to 50% reduction in hemoglobin ( Leo and Johannes, 2021 ), again demonstrating that monotherapy toxicity of PARP1/2 inhibitors may be dependent on PARP2 inhibition. Furthermore, according to a subsequent rat in vivo study of combination chemotherapy, AZD5305 + carboplatin showed improved serologic tolerance compared with olaparib + carboplatin, as peripheral reticulocytes and myeloid erythroid precursor cells recover with continuous AZD5305 administration but not in the presence of continuous olaparib ( Gill et al, 2021 ). Notably, this differentiation was maintained and confirmed again in a more closely mimic clinical protocol with two-weekly cycles and higher dose of carboplatin ( Gill et al, 2021 ).…”
Section: Parp1-selective Inhibitor Azd5305mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bone marrow examination at day 14 revealed a similar level of erythroid bone marrow precursors and bone marrow cellularity for rats treated with AZD5305 plus carboplatin compared with those treated with carboplatin alone. 39 Similar red blood cell and platelet nadir-to-recovery patterns for AZD5305 and first-generation PARP inhibitors were demonstrated when rats were dosed with daily AZD5305 plus carboplatin at a higher dose for two thrice-weekly cycles to mimic the clinical conditions of treatment. Even at increased carboplatin dose and duration of combination therapy, red blood cell and platelet recovery was significantly more rapid for AZD5305 compared with other PARP inhibitors.…”
Section: Combination Strategies Of Azd5305 With Chemotherapymentioning
confidence: 80%
“…34 In rat models, olaparib dosed daily for 2 weeks led to a 50% reduction in hemoglobin, consistent with the anemia often observed among patients in the clinic. 39 Yet, when AZD5305 was dosed under identical experimental conditions, using a dose predicted to be clinically efficacious, no cytopenias were noted. 39 Peripheral blood reticulocyte levels were also maintained in rats treated with AZD5305 throughout the 2-week period of treatment, compared with rats treated with first-generation PARP inhibitors, which suffered significant reductions both in peripheral reticulocytosis, as well as in intramedullary erythroid precursor cells measured using flow cytometry.…”
Section: Hematologic Toxicity Of Azd5305 Compared With First-generati...mentioning
confidence: 97%